THE IMPACT OF PHYSICAL ACTIVITY ON INTRAOCULAR PRESSURE: A REVIEW OF THE LITERATURE - Marjanovic, Ivan; Vasovic, Dolika; Maric, Vesna; Raskovic, Andrijana; Marjanovic, Marija; Milivojevic, Milorad (Medical Research, 2026)
Glaucoma is a chronic, progressive optic neuropathy and one of the leading causes of irreversible blindness worldwide. Intraocular pressure (IOP) remains the most important and only proven modifiable risk factor for the development and progression of glaucoma. Physical activity exerts a wide range of systemic effects that may directly or indirectly influence IOP and ocular perfusion. The effect of physical activity on IOP depends on the type, intensity, and duration of exercise, as well as individual patient characteristics.Aerobic exercise is consistently associated with acute IOP reductions of 1 to 5 mmHg, mediated by increased aqueous humor outflow, osmotic shifts, and sympathetic modulation of aqueous production. Long-term aerobic training may produce sustained baseline IOP reductions of approximately 2 to 4 mmHg, with concurrent improvements in ocular perfusion pressure. In contrast, high-intensity anaerobic and isometric exercise, as well as inverted body positions such as specific yoga postures, can transiently elevate IOP to clinically concerning levels, primarily through Valsalva maneuver-induced increases in episcleral venous pressure. The relationship between physical activity and ocular perfusion pressure further underscores the complexity of exercise-ocular interactions. The clinical significance of these findings lies in the potential application of physical activity as an adjunctive strategy in glaucoma management. Moderate aerobic exercise should be encouraged in most patients, while certain high-intensity activities and inverted positions should be carefully considered. Further research is needed to establish standardized guidelines and to better understand the long-term impact of physical activity on glaucoma progression.
Keywords: intraocular pressure, glaucoma, physical activity, aerobic exercise, ocular perfusion pressure